Predictors of meeting physical activity and fruit and vegetable recommendations in 9–11-year-old children. (March 2015) - Beck, Jimikaye; De Witt, Peter; McNally, Janise; Siegfried, Scott; Hill, James O; Stroebele-Benschop, Nanette
Objective: Childhood obesity represents a significant public health problem. This study examined physical activity and nutrition behaviours and attitudes of 9–11-year-olds, and factors influencing these behaviours. Design: Study participants recorded pedometer steps for 7 days and completed physical activity enjoyment, food attitudes and food frequency questionnaires. Fruit and vegetable sales data were collected from schools. The setting for the study was elementary schools in metropolitan Denver, Colorado (USA). Method: Logistic regression was used to determine significant predictors of meeting physical activity/fruit and vegetable intake recommendations. Results: Overall, 42.0% of boys and 44.1% of girls met step count recommendations. Further, 30.9% of boys and 32.8% of girls met step count requirements associated with low risk for overweight/obesity. Enjoyment of physical activity significantly predicted achieving recommendations. Overall, 66.4%, 51.3% and 65.8% of 9–11-year-olds achieved adequate fruit, vegetable, or fruit and vegetable intake, respectively. Enjoyment of fruit/vegetable consumption, perceived parental intake and encouragement and cups of vegetables purchased predicted achieving adequate intake. Conclusion: The majority of young people aged 9–11 years failed to meet step count recommendations to prevent the risk for overweight/obesity. A significant proportion also failed to achieve adequate fruit and/or vegetable intake. Future programmes and interventions should affect multiple environments in order to improve child enjoyment of physical activity and fruit/vegetable intake in order to improve the physical, mental and emotional health of children.